Shared decision-making competency and its associated factors among palliative care nurses: a cross-sectional study in China - Junchen Guo; Sishan Jiang; Yunyun Dai; Xianghua Xu; Chaoyi Liu; Yongyi Chen (BMC Nursing)
Abstract Background The role of nurses in shared decision-making (SDM) within the healthcare decision-making process has increasingly gained attention The ability of nurses to engage in effective SDM can significantly impact patient outcomes and satisfaction with care. Given the palliative care continues to evolve, this study aimed to investigate the level of SDM competency and explore associated factors among palliative care nurses in China. Methods A cross-sectional study was conducted between June and July 2024. The convenience sample was recruited from five online Chinese palliative care nurse groups. Anonymous data were collected through a self-designed sociodemographic questionnaire, the Shared Decision-Making Competency Scale (SDMCS) and the Empathy Ability Scale (EAS). Multivariate linear regression was performed to explore the factors associated with SDM competency. Results A total of 429 palliative care nurses from 30 provinces or municipalities across China participated in this study. The Chinese palliative care nurses had a high level of SDM competency (mean total SDMCS 211.72 ± 25.75) and high empathic ability (EA), (mean total EAS 132.63 ± 20.30). There was a positive correlation between EA and SDM competency (r = 0.704, P < 0.01). The EA (β = 0.683, P<0.001), experiences of SDM training (β=-0.155, P<0.001) and educational background (β=-0.142, P = 0.007) were statistically significant factors influencing nurses’ SDM competency based on multiple linear regression analysis. These associated factors could explain 55.4% of the difference in SDM competency. Conclusions This study found that palliative care nurses in China exhibited high levels of SDM competency and a high level of EA. Nurses with postgraduate education, SDM training experience, and high EA demonstrated higher levels of SDM competency compared to those without these attributes. The findings underscore the importance of incorporating structured SDM training programs in nursing education and professional development initiatives, particularly focused on building empathy skills.